Community-Led Research Priority Setting for Highly Vulnerable Communities: Adaptation of the Research Prioritization by Affected Communities Protocol. (24th September 2020) - Altman, Molly R.; Kim, Jane; Busse, Morgan; Kantrowitz-Gordon, Ira
While community engagement can occur at all levels of research development, implementation, and dissemination, there is a great need for participation from those with lived experience in the development of research priorities to be used by stakeholders in research, funding, and policy. The Research Prioritization by Affected Communities (RPAC) protocol has successfully developed community-driven priorities for those at risk for preterm birth, but the 2-day focus group methodology may not be suitable for all vulnerable communities. For the purposes of a larger study supporting pregnant and parenting individuals with opioid use disorder (OUD) in research prioritization, we adapted the RPAC protocol to meet the needs of this highly stigmatized community. This adaptation made it possible for those who may not have been able to attend two separate sessions to successfully engage in this participatory process and produce a completed set of priorities by the end of 1 day. The objective of this article is to validate the adapted protocol for prioritizing research and service delivery needs with vulnerable and stigmatized communities.